Case report: Two cases of prostate adenocarcinoma progressing to rare sarcomatoid carcinoma with normal PSA levels following endocrine therapy - Dai, Zhicheng; Wang, Weikang; Guan, Haifang; Wang, Xiaohui; Ren, Yongheng; Qiu, Ying (Frontiers in Oncology, 2024)
BackgroundPatients with prostate adenocarcinoma undergoing regular endocrine therapy may maintain normal PSA levels during follow-up, yet still progress to the highly malignant and rare prostatic sarcomatoid carcinoma, which is seldom reported. This article presents two case studies of prostatic sarcomatoid carcinoma. To date, only a few publications have described prostatic sarcomatoid carcinoma, and the clinical, morphological, and molecular dimensions of prostate adenocarcinoma warrant further investigation.Case descriptionPatient A was admitted two years ago due to difficulty urinating, with a PSA level of 6.35 ng/ml. A prostate needle biopsy was performed, and the postoperative pathology diagnosed prostate adenocarcinoma with a Gleason score of 9 (5 + 4, grade group 5). Citing personal reasons, the patient declined a radical prostatectomy and instead received ongoing androgen deprivation therapy (ADT), comprising goserelin, abiraterone, and prednisone. During follow-up, regular PSA tests showed no abnormalities. One year ago, the patient was admitted again due to difficulty urinating and hematuria, choosing to address only the urethral obstruction. Transurethral resection of the prostate was performed, and the postoperative pathology diagnosed sarcomatoid carcinoma of the prostate. Patient B was admitted three years ago due to difficulty urinating accompanied by hematuria. A prostate MRI and a whole-body radionuclide bone scan suggested prostate cancer with bone metastasis. Prostate needle biopsy confirmed the diagnosis. The patient was then regularly treated with androgen deprivation therapy, using goserelin. Throughout the follow-up period, the PSA levels consistently remained within normal limits. One year ago, the patient was admitted due to rectal bleeding. It was speculated that the symptoms of rectal bleeding might have been caused by the prostate cancer invading the rectal wall. A prostate needle biopsy was performed, and the pathology diagnosed sarcomatoid carcinoma of the prostate.ConclusionsThis case underscores the inadequacy of relying solely on PSA levels to monitor high-grade prostate adenocarcinoma during endocrine therapy, as patients may progress to highly malignant atypical variants despite normal PSA levels. We propose that for high-grade prostate cancer patients who are unable to undergo radical prostatectomy, regular and frequent MRI screenings or repeat biopsies should be integral during endocrine therapy and follow-up. Furthermore, a detailed review of the patient’s treatment history and clinical data, including immunohistochemical findings, might offer deeper clinical insights into prostatic sarcomatoid carcinoma.